2008
DOI: 10.1093/jmedent/45.4.751
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aerial Spraying of Pyrethrin Insecticide onCulex pipiensandCulex tarsalis(Diptera: Culicidae) Abundance and West Nile Virus Infection Rates in an Urban/Suburban Area of Sacramento County, California

Abstract: In response to an epidemic amplification of West Nile virus (family Flaviviridae, genus Flavivirus, WNV), the Sacramento and Yolo Mosquito and Vector Control District (SYMVCD) sprayed ultralow-volume (ULV) formulations of pyrethrin insecticide (Evergreen EC 60-6: 6% pyrethrin insecticide, 60% piperonylbutoxide; MGK, Minneapolis, MN, applied as 0.003 kg/ha [0.0025 lb/acre] ) over 218 km2 in north Sacramento and 243.5 km2 in south Sacramento on three consecutive evenings in August 2005. We evaluated the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Despite this, many authors have suggested that more frequent ULV adulticiding may be necessary to alter viral transmission dynamics (Andis et al 1987, Pawelek et al 2014. It is interesting to note that some of the only papers that have demonstrated a clear reduction in viral prevalence from ULV treatments in vector mosquitoes conducted aerial treatments over 3 sequential nights (Elnaiem et al 2008, Macedo et al 2010. The work presented here further supports the notion that multiple ULV treatments, timed to account for cohorts of mosquitoes transitioning into and out of susceptibility, may yield a greater reduction in viral transmission and vector populations than isolated ULV treatments (Andis et al 1987).…”
Section: Variablementioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, many authors have suggested that more frequent ULV adulticiding may be necessary to alter viral transmission dynamics (Andis et al 1987, Pawelek et al 2014. It is interesting to note that some of the only papers that have demonstrated a clear reduction in viral prevalence from ULV treatments in vector mosquitoes conducted aerial treatments over 3 sequential nights (Elnaiem et al 2008, Macedo et al 2010. The work presented here further supports the notion that multiple ULV treatments, timed to account for cohorts of mosquitoes transitioning into and out of susceptibility, may yield a greater reduction in viral transmission and vector populations than isolated ULV treatments (Andis et al 1987).…”
Section: Variablementioning
confidence: 99%
“…Finally, trapping mosquitoes over a large area for an extended time with conventional trapping technologies is extremely labor intensive and expensive. For this reason, evaluations of the effectiveness of ULV adulticides on natural adult mosquito populations do exist but are limited (Mitchell et al 1970, Chadeeq 1985, Andis et al 1987, Fox and Specht 1988, Elnaiem et al 2008, Sudsom et al 2015, Stoddard 2018. Other strategies for assessing the effect of ULV treatments on mosquito populations have relied on egg counts or immature mosquito counts to detect changes in the population after a treatment with notably mixed results (Andis et al 1987, Chua et al 2005, Reddy et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…That the populations at the seven colonies where we recorded productivity in 2020 were higher than elsewhere in Sacramento could be an indication of better habitat quality or lower rates of infection. Dead magpies infected with West Nile virus, however, were reported near our study areas only from mid-June through mid-September (n = 27, https://www.fightthebite.net/media/west-nile-virusactivity/), after the nesting season, when mosquitoes are more abundant (Elnaiem et al 2008, Macedo et al 2010…”
Section: Productivity Of Successful Nestsmentioning
confidence: 92%
“…Susceptible Cx. tarsalis utilized in insecticide CDC bottle bioassays described below were from the Kern National Wildlife Refuge (KNWR) colony [16, 17] and resistant Cx. tarsalis maintained in an insectary that were originally collected during 2019 in Woodland, California USA (Conaway strain; GPS coordinates: 38.647287, -121.668173).…”
Section: Methodsmentioning
confidence: 99%